Pengaruh International Event terhadap Pelayanan Lalu Lintas Penerbangan di AirNav Indonesia Cabang Lombok - Aisyah Rahmayani; Djoko Jatmoko (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This study aims to analyze the impact of international events on air traffic services. To what extent do spikes in traffic and international event activities affect service quality, and provide new insights. The study was conducted during the implementation of MotoGP and World Superbike International on Lombok Island, and data processing was carried out at AirNav Indonesia Lombok Branch. The analysis method used is a quantitative method. The population includes all air traffic control personnel on duty at Zainuddin Abdul Madjid International Airport. This study uses a total sampling technique. Data collection was carried out through observation studies, questionnaires, interviews and literature studies containing flight data both taking off and landing during the event. The questionnaire distributed focused on personnel services during this event. The results show that there is an influence of international events on air traffic services with a T-test value on the sample of 0.0001.